Stabilisation of Pit Slopes, Waikaka Alluvial Gold Mine (The Australasian Institute of Mining and Metallurgy, 2002)
Wet mining of auriferous gravels at L & MÆs Waikaka operation in Southland creates spoil dumps derived from stripping of a clay rich overburden, tailings from past dredging and the processing of auriferous sands and gravels. Over recent times, spoil dumps have slumped on six occasions, threatening the viability of the wet mining operation. Close examination of slump morphology, coupled with the sequence of material placement and rate of dumping suggested a mechanism associated with undrained failure of a 2 m layer of silt and sand tails forming the base of dumps.Commencing with some information on the geotechnical properties of source overburden, back analysis of failure morphology and sequence and development of undrained loading conditions from first principals, the most likely failure mechanism and factors controlling failure were defined. Based on analysis results, a scheme to stabilise the lowwall dumps was developed and implemented, augmented by continuous monitoring of pore pressures in the basal wet tails, and laboratory testing for confirmation of computed material properties.Lowwall spoil stability has improved since implementation involving changes to the method of spoil loading, and modification of wet tails composition to improve permeability and drainage of the basal wet tails under load. The method and approach to prediction and verification of failure mechanism provide a sound basis for continued mining of deeper auriferous gravels.